Answer:
Center of sphere = (2, 0, -6)
Radius of sphere = [tex]\dfrac{9}{\sqrt2}\text{ units}[/tex]
Step-by-step explanation:
We are given the following in the question:
Equation of sphere:
[tex]2x^2+2y^2+2z^2=8x-24z+1[/tex]
Formula:
The equation of sphere is of the form
[tex](x-a)^2 + (y-b)^2 + (z-c)^2 = r^2\\\text{where (a,b,c) is the center of sphere and r is the radius of sphere.}[/tex]
Simplifying the given equation we get,
[tex]2x^2+2y^2+2z^2=8x-24z+1\\\text{Dividing by 2}\\x^2 + y^2 + z^2 = \dfrac{1}{2} + 4x - 12z\\\\x^2 -4x + y^2 + z^2+12z = \dfrac{1}{2}\\\\\text{Adding 4 and 36 on both sides, we get,}\\\\x^2-4x + 4 +y^2+ z^2+12z + 36 = \dfrac{1}{2} + 4+ 36\\\\(x-2)^2 + (y-0)^2 + (z+6)^2 = \dfrac{81}{2}\\\\\text{Comparing with the equation of sphere}\\a = 2\\b = 0\\c = -6\\\\r^2 = \dfrac{81}{2}\\\\r = \sqrt{\dfrac{81}{2}}= \dfrac{9}{\sqrt2}[/tex]
Center of sphere = (2, 0, -6)
Radius of sphere = [tex]\dfrac{9}{\sqrt2}\text{ units}[/tex]